2016
DOI: 10.22256/pubvet.v16n11.1325
|View full text |Cite
|
Sign up to set email alerts
|

Perception of consumer market towards the welfare of production animals in Piracicaba, Sao Paulo, Brazil

Abstract: Catarina (UDESC), em Chapecó-SC. Atualmente afastada para o doutoramento junto ao NUPEA/ESALQ. 3 Biológo -Bacharel em Ciëncias Biológicas, ESALQ/USP -2010. Mestrando -NUPEA/ESALQ/USP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…For example, the study by Franchi et al (2012a) in Piracicaba (state of São Paulo) it was found that more than 90% of consumers stated that they were aware that production animals expressed feelings, although high perception on the subject, only 36.9% of consumers take this into account when purchasing the product. However, there has been a steady increase in this value, due to access to information about the way animals are raised.…”
Section: Concern About Animal Welfarementioning
confidence: 99%
“…For example, the study by Franchi et al (2012a) in Piracicaba (state of São Paulo) it was found that more than 90% of consumers stated that they were aware that production animals expressed feelings, although high perception on the subject, only 36.9% of consumers take this into account when purchasing the product. However, there has been a steady increase in this value, due to access to information about the way animals are raised.…”
Section: Concern About Animal Welfarementioning
confidence: 99%
“…However, when purchasing animal-based products aspects in addition to product quality must be considered. Actions related to ethical consumption, especially in more developed countries of which some are buyers of Brazilian meat, this issue have been constantly evaluated by the population (FRANCHI et al, 2012).…”
Section: Introductionmentioning
confidence: 99%